Bacteriophobic Zwitterionic/Dopamine Coatings for Medical Elastomers (Adv. Mater. Interfaces 30/2022). Issue 30 (26th October 2022) - Texidó, Robert; Cabanach, Pol; Kaplan, Richard; García‐Bonillo, Cristina; Pérez, Darío; Zhang, Shuo; Borrós, Salvador; Pena‐Francesch, Abdon
Abstract : Anti‐Biofouling Coatings In article number 2201152, Robert Texidó, Pol Cabanach, Abdon Pena‐Francesch, and colleagues use a coating strategy combining dopamine and zwitterionic polymers to prevent bacteria from adhering to soft and flexible materials commonly used in medical devices. The coatings exhibit superhydrophilic and anti‐biofouling properties, leading to a >99% reduction in bacterial adhesion. This bacteriophobic coating is implemented in a commercial urinary catheter, reducing bacterial adhesion by 2 orders of magnitude, and avoiding bacterial colonization to prevent catheter‐associated urinary tract infections.